(untitled) (Journal of Engineering, 2010)
The development of monitoring systems for rotating blade has been driven by a desire to reduce the maintenance costs and human interaction to improve the safety, reliability and operational life, so it is urgent to monitor the integrity of a structural systems. In this study four different coordinate system has been used to describe the blade motion, then an element stiffness and mass matrices has been formulated by using Hamilton’s principle and finite element method, where each element has been described by seven degrees of freedom, so the method has been demonstrated analytically on a finite element model to estimate the modal parameters under rotating and non-rotating conditions in vacuum (to eliminate aerodynamic effect and damping coefficient) and to capture centrifugal effect, so the damage has been simulated by stiffness reduction of assumed elements and by crack form. These results was reasonable, so many parameters has been investigated such as, damage severity, damage location and the effect of rotation speed on these methods have been studied, as well as an assessment has been provided for these methods via statistic to suggest the effective method and this is the main objective, so The Residual Error Method was the best,compared with other methods. All formulations and computations has been coded m MATLAB version 7.